Numerical modelling of the impact of leakage under divertor baffle in WEST. (October 2022) - Yang, H.; Ciraolo, G.; Bucalossi, J.; Bufferand, H.; Fedorczak, N.; Tamain, P.; Falchetto, G.; Rivals, N.; Gunn, J.P.; Marandet, Y.; Pégourié, B.; Vartanian, S.; et al.
Abstract: In WEST experimental campaign C5, the divertor pumping capability has been improved by sealing the space between the divertor outer baffle and the vacuum vessel. It is expected that the degree of baffle leakage influences the transport of neutral particles inside the main chamber, which affects the detachment onset. Knowing the exact impacts of leakage and understanding the physical processes behind it are helpful for the study and control of plasma detachment. We investigate the impact of leakage by performing transport simulations through SOLEDGE-EIRENE code considering several cases with different leakage levels. Starting from the basic simulation case, non-constant radial transport coefficients obtained by the feedback control method are applied to achieve a better match with the experimental one (#54903) in L-mode. Based on the basic case, the evolution of plasma regimes from sheath limited regime to detached one in different wall geometries has been studied by ramping the upstream density. The numerical results show that the cases with closed or reduced leakage under the baffle have better performance in trapping the neutral particles and higher neutral pressure near the baffle. The neutral compression ratio is increased by a factor up to 4, leading to more significant momentum and power dissipation in the divertor, thus lowering the detachment threshold in n e, sep by up to 16%. At the same time, a much higher gas puff rate by a factor up to 22 is needed to maintain an equivalent n e, sep level in the case without or reduced leakage. For all the cases here, there exist characteristic parameters on which the baffle closure has no obvious influence on their value when plasma starts to detach. The evolution of radiator height as a function of target temperature shows no sensitivity to the leakage, which gives some insight into the stable detachment control strategy in the future. Finally, simulation results are compared with available neutral pressure measurements from WEST campaigns to verify the predictions from the simulation. Highlights: The impact of baffle leakage in WEST is investigated with SOLEDGE-EIRENE simulation. The anomalous transport coefficients are adjusted by the feedback control method. The case with less leakage has lower detachment threshold in upstream density. The detachment threshold in some parameters shows no sensitivity to variated leakage. The simulation results are compared with available experimental data.